Clickable Cisplatin Derivatives as Versatile Tools to Probe the DNA Damage Response to Chemotherapy - Moretton, Amandine; Slyskova, Jana; Simaan, Marwan E.; Arasa-Verge, Emili A.; Meyenberg, Mathilde; Cerrón-Infantes, D. Alonso; Unterlass, Miriam M.; Loizou, Joanna I. (Frontiers in Oncology, 2022)
Cisplatin induces DNA crosslinks that are highly cytotoxic. Hence, platinum complexes are frequently used in the treatment of a broad range of cancers. Efficiency of cisplatin treatment is limited by the tumor-specific DNA damage response to the generated lesions. We reasoned that better tools to investigate the repair of DNA crosslinks induced by cisplatin would therefore be highly useful in addressing drug limitations. Here, we synthesized a series of cisplatin derivatives that are compatible with click chemistry, thus allowing visualization and isolation of DNA-platinum crosslinks from cells to study cellular responses. We prioritized one alkyne and one azide Pt(II) derivative, Pt-alkyne-53 and Pt-azide-64, for further biological characterization. We demonstrate that both compounds bind DNA and generate DNA lesions and that the viability of treated cells depends on the active DNA repair machinery. We also show that the compounds are clickable with both a fluorescent probe as well as biotin, thus they can be visualized in cells, and their ability to induce crosslinks in genomic DNA can be quantified. Finally, we show that Pt-alkyne-53 can be used to identify DNA repair proteins that bind within its proximity to facilitate its removal from DNA. The compounds we report here can be used as valuable experimental tools to investigate the DNA damage response to platinum complexes and hence might shed light on mechanisms of chemoresistance.